2023
DOI: 10.1039/d2ma01015a
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering of PDMS for improved triboelectrification

Abstract: Here we demonstrate the approach for improving the triboelectric charge in contact-separation of identical PDMS contact layers by three orders of magnitude. It is achieved by functionalization with self-assebled monolayers...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The observations suggested that for selecting CE pairs according to electron-transfer reactions, the total reaction energy for each combination of materials and deformation range of interest should be considered instead of a single triboelectric series (Tables S1 and S2). Accordingly, the most efficient combination would be APTS/FOTS and APTS/TMSPMA, in agreement with experimental results. , However, a difference in terms of distinctly electropositive electron-transfer reaction energies for PDMS and electronegative CE response according to experimental ref is also observed. To this end, it should be noted that both the O- and Si-terminated residues yield negative electron affinities in distinction to the positive value for a pristine TDMS molecule (Table S3).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The observations suggested that for selecting CE pairs according to electron-transfer reactions, the total reaction energy for each combination of materials and deformation range of interest should be considered instead of a single triboelectric series (Tables S1 and S2). Accordingly, the most efficient combination would be APTS/FOTS and APTS/TMSPMA, in agreement with experimental results. , However, a difference in terms of distinctly electropositive electron-transfer reaction energies for PDMS and electronegative CE response according to experimental ref is also observed. To this end, it should be noted that both the O- and Si-terminated residues yield negative electron affinities in distinction to the positive value for a pristine TDMS molecule (Table S3).…”
Section: Resultssupporting
confidence: 86%
“…Accordingly, the most efficient combination would be APTS/FOTS and APTS/TMSPMA, in agreement with experimental results. 4,22 However, a difference in terms of distinctly electropositive electrontransfer reaction energies for PDMS and electronegative CE response according to experimental ref 3 is also observed. To this end, it should be noted that both the O-and Si-terminated residues yield negative electron affinities in distinction to the positive value for a pristine TDMS molecule (Table S3).…”
Section: Comparison Of Electronegativities and Electropositivitiesmentioning
confidence: 81%
See 2 more Smart Citations
“…The addition of MCC in the composite correlates to an increase in the roughness, it steadily increased to 175.6 ± 24.5 nm for 70 wt.% MCC composite due to presence of pores and particles on surface. While changes in surface roughness may indeed contribute to increased surface charge density, [ 37,41,42 ] we are confident that the main contributing factor in this case is the difference in mechanical properties due to filler addition.…”
Section: Resultsmentioning
confidence: 81%